Construction and Characterization of a Fluorescently Labeled Infectious Human Immunodeficiency Virus Type 1 Derivative - Müller, Barbara (American Society for Microbiology, 2004)
The introduction of a label which can be detected in living cells opens new possibilities for the direct analysis of dynamic processes in virus replication, such as the transport and assembly of structural proteins. Our aim was to generate a tool for the analysis of the trafficking of the main structural protein of human immunodeficiency virus type 1 (HIV-1), Gag, as well as for the analysis of virus-host cell interactions in an authentic setting. We describe here the construction and characterization of infectious HIV derivatives carrying a label within the Gag polyprotein. Based on our initial finding that a short epitope tag could be inserted near the C terminus of the matrix domain of Gag without affecting viral replication, we constructed HIV derivatives carrying the egfp gene at the analogous position, resulting in the expression of a Gag-EGFP fusion protein in the authentic viral context. Particles displaying normal viral protein compositions were released from transfected cells, and Gag-EGFP was efficiently processed by the viral protease, yielding the expected products. Furthermore, particles with mature morphology were observed by thin-section electron microscopy. The modified virus was even found to be infectious, albeit with reduced relative infectivity. By preparing mixed particles containing equimolar amounts of Gag-EGFP and Gag, we were able to obtain highly fluorescently labeled virion preparations which displayed normal morphology and full wild-type infectivity, demonstrating that the process of HIV particle assembly displays a remarkable flexibility. The fluorescent virus derivative is a useful tool for investigating the interaction of HIV with live cells.